Association between Hp infection and serum uric acid to high-density lipoprotein cholesterol ratio in adults - Qin, Zihan; Fang, Yinuo; Liu, Yifei; Zhang, Lingye; Zhang, Ruoyi; Zhang, Shutian (Frontiers in Medicine, 2025)
BackgroundHelicobacter pylori (Hp) infection is one of the major global health problems resulting in multiple system disorders. The serum uric acid to high density lipoprotein cholesterol ratio (UHR) is a novel index of inflammation and metabolism, but its association with the development of Hp infection is still unclear.Materials and methodsThis is a cross-sectional study involving 2,666 participants, using data from the National Health and Nutrition Examination Survey (NHANES) conducted in the United States. The relationship between UHR and Hp infection was evaluated by multivariate logistic regression and sensitivity analysis to enhance the stability of the results.ResultsAmong all individuals, 1,165 were Hp positive (43.7%) and 1,501 were Hp negative (56.3%). After adjustment, there was a positive correlation between UHR and Hp infection (OR = 1.15; 95% CI 1.02–1.30; P = 0.020). This association is relatively stable in the subgroup analysis (P > 0.05).ConclusionThere is a positive correlation between the UHR and the development of Hp infection in our study. This non-invasive indicator can improve the ability to monitor Hp infection and may find alternative therapeutic intervention targets.